Research at school: a pending issue (Journal of Parents and Teachers, 2025)
We may associate the word “research” with complicated activities, people in white coats, surrounded by endless documents. However, we should promote it among students from primary school onwards. And we are referring to proper research, with real facts, not simply looking up information in books. The starting point, the research topic, could be their own comments or interests, or a news item from the newspaper. This would be followed by data collection and interpretation, choosing a sample, and concluding by sharing their findings. In this way, more active and experiential learning is developed.
Keywords: research, school, search, data, active learning